Chad : Staff Report for the 2001 Article IV Consultation, Third Review Under the Second Annual Program Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Augmentation of Access and for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report, 2002)
This paper examines Chad's 2001 Article IV Consultation, Third Review Under the Second Annual Program Under the Poverty Reduction and Growth Facility, and Requests for Augmentation of Access and for Waiver of Performance Criteria. Chad has had a reasonably good year in 2001, reversing the policy slippages in 2000. Economic performance, including in the area of governance, has improved measurably. Growth prospects are also good, with real GDP projected to grow at an annual rate of 10 percent in 2001-03.